Studies on the feeding habits of Lutzomyia (N.) intermedia (Diptera, Psychodidae), vector of cutaneous leishmaniasis in Brazil Estudos sobre os hábitos alimentares de Lutzomyia (N.) intermedia (Diptera, Psychodidae), vetor de leishmaniose cutânea no Brasil - Margarete Martins dos Santos Afonso; Almério Castro Gomes; Cláudio Roberto Valente Meneses; Elizabeth Ferreira Rangel (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
The precipitin test was applied to identify the blood meal sources of Lutzomyia intermedia, collected in two distinct habitats: inside houses and in the peridomicile, in Mesquita, Rio de Janeiro State, Brazil, a transmission area of Leishmania (V.) braziliensis. The following antisera were tested: human, avian, equine, rodent, and opossum. From a total of 370 females analyzed, 128 specimens from the domicile and 59 from the peridomicile reacted with specific antisera. The anthropophily of L. intermedia was confirmed in both habitats; likewise, the feeding of this sand fly species on domestic animals, observed in previous entomological surveys, was confirmed by the strong reactivity with avian, canine, and equine antisera. However, feeding on rodents, mammals frequently found inside and around houses, represents further evidence related to the vector competence of L. intermedia, since synanthropic and sylvatic rodents have been considered a putative reservoir of L. (V.) braziliensis. O teste de precipitina foi aplicado na identificação das fontes alimentares de Lutzomyia intermedia, de ambientes intra e peri-domiciliar, do Município de Mesquita, Estado do Rio de Janeiro, Brasil, área de transmissão de Leishmania (V.) braziliensis. Foram testados os seguintes antisoros: homem, ave, cão, eqüino, gambá e roedor. De um total de 370 fêmeas analisadas, revelaram reatividade, contra os antisoros testados, 128 espécimes do intra-domicílio e 59 do ambiente peridomiciliar. A antropofilia de L. intermedia foi confirmada nos dois ambientes trabalhados; da mesma forma, a alimentação deste flebotomíneo em animais domésticos, observada anteriormente em levantamentos entomológicos, foi comprovada pela forte reatividade com antisoros de ave, cão e eqüino. Entretanto, a alimentação em roedores, animais sinantrópicos no ambiente domiciliar (interior e ao redor das residências), é mais uma forte evidência da competência vetorial de L. intermedia, uma vez que roedores sinantrópicos e silvestres são comprovadamente reservatórios de L. (V.) braziliensis.